2016
DOI: 10.1021/acs.macromol.6b00926
|View full text |Cite
|
Sign up to set email alerts
|

Directed Assembly of Quantum Dots Using Brush Block Copolymers for Well-Ordered Nonlinear Optical Nanocomposites

Abstract: We report the directed assembly of quantum dots (QDs) within wellordered photonic nanocomposites using a family of (polynorbornene-graf tpoly(styrene))-block-(polynorbornene-graf t-poly(ethylene oxide)) (PS-b-PEO) brush block copolymers (BBCPs). Cadmium selenide (CdSe) nanoparticles (NPs) modified with 11-mercaptoundecylhydroquinone are selectively incorporated within the PEO domains of the self-assembled BBCPs via strong hydrogen-bonding interactions between the ligands on QDs and PEO brushes of the BBCPs. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 60 publications
(103 reference statements)
0
40
0
Order By: Relevance
“…Watkins and co‐workers have demonstrated that BBCPs can accommodate high NP loading concentrations by designing strong, preferential interactions between NPs and one block of a BBCP. These interactions prevent NP aggregation and promote uniform distribution of the NPs in one domain …”
Section: Strategies Toward Tuning Of Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Watkins and co‐workers have demonstrated that BBCPs can accommodate high NP loading concentrations by designing strong, preferential interactions between NPs and one block of a BBCP. These interactions prevent NP aggregation and promote uniform distribution of the NPs in one domain …”
Section: Strategies Toward Tuning Of Optical Propertiesmentioning
confidence: 99%
“…Song et al have investigated the incorporation of gold NPs into polystyrene/poly(ethylene oxide) (PS‐ b ‐PEO) BBCPs (Figure ). [55c] Gold NPs with ≈2 nm core diameter supported by 4‐mercaptophenol ligands were utilized, as strong hydrogen‐bond interactions with these ligands allow for the selective incorporation of gold NPs in the PEO domains of these BBCPs. Composite films with NP loadings as high as 67.2 wt% (Au% = 48.4 wt%) could be prepared by drop casting THF solutions of BBCPs and gold NPs.…”
Section: Strategies Toward Tuning Of Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sophisticated design provides superstructures with physicochemical properties, which are not only superior, but also do not arise in the constituent particles. Popular choices include quantum dots, plasmonic metal nanoparticles, and magnetic nanoparticles . These particles exhibit important physical properties related to technological applications, however, they are extremely difficult to synthesize in larger quantities with uniform size, shape, and chemical constituents.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] As a result, the BBCP architecture has been effectively used for the development of next generation photonic materials, metallo-dielectric materials, porous templates, and ordered nanoparticle arrays. [10][11][12][13][14][15] NPs are generally incorporated into the BCP microstructure through either an in-situ reduction of inorganic precursors, or through a co-assembly of the BCP with exsitu synthesized NPs. 3 During co-assembly, NPs can be sequestered into a specific BCP domain through strong intermolecular interactions between surface ligands on the NPs and the polymer chains of a specific block.…”
Section: Introductionmentioning
confidence: 99%